to prove

Η * Η’ = Η’ * Η

Η= [a b]

[c d]

H'=[a' b']

[c' d']

Printable View

- November 2nd 2010, 04:38 AMstollaMatrix multiplication.
to prove

Η * Η’ = Η’ * Η

Η= [a b]

[c d]

H'=[a' b']

[c' d'] - November 2nd 2010, 04:42 AMUnknown008
Do the multiplication matrix and show us what you get! (Smile)

- November 2nd 2010, 04:49 AMstolla
i Do the multiplication and i find a='a and d='d

but my teacher say a’ = a b’ = c c’ = b and d’ = d - November 2nd 2010, 05:09 AMUnknown008

And

Well, I'm not sure what you are trying to do, but your original post says prove that H.H' = H'.H

Since we know that a = a', d = d', c = b' and b = c', then H.H' = H'.H is proved. - November 2nd 2010, 06:09 AMstolla
we dont know that a = a', d = d', c = b' and b = c',

we are trying to find that h*h'=h'*h

and i think that the anser is a = a', d = d', c = b' and b = c',

but i am not completely sure - November 2nd 2010, 06:11 AMUnknown008
Well, for H.H' to be equal to H'.H, we must have a = a', d = d', c = b' and b = c'

- November 2nd 2010, 06:16 AMstolla
thnks dude!

may the force be with you!! - November 2nd 2010, 06:18 AMUnknown008
Uh...okay... (Itwasntme)

Thanks! - November 2nd 2010, 06:19 AMstolla
sorry can you explain the answer plzzzzz??

- November 2nd 2010, 06:24 AMUnknown008
You cannot prove that

H.H' = H'H

unless we know that a = a', d = d', c = b' and b = c' - November 2nd 2010, 07:38 AMHallsofIvy
All you appear to have here is two unrelated matrices, H and H'.

You**cannot**then prove that "H*H'= H'*H" because it is not true: matrix multiplication is not commutative.

Or did you mean that H' is the**transpose**of H? No, that doesn't work either. So I don't know what you are asking.